Philosophical Meaning for Justice Based on the One Godhead in Judge's Decision - Wahyudi Kurniawan; Sholahuddin Al-Fatih (Faculty of Law, Universitas Pekalongan, 2021)
This study aims to analyze the meaning of philosophy in the court decision